In vitro Study of the Antibiofilm Potential of Bay Leaf Extract (Syzygium polyanthum (Wight) Walp) against Streptococcus sanguinis and Streptococcus mutans - Listiana Masyita Dewi; Azka Tarisa Atmaja; Muhammad Marcelliano Rifky Aditomo Putra; Devi Usdiana Rosyidah; Nurhayani Nurhayani; Rima Munawaroh (Biology, Medicine, & Natural Product Chemistry, 2026)
The ability to form biofilms is one of the characteristics of microbes that has the potential to cause antimicrobial resistance. The oral cavity environment, which is frequently exposed to external environments and has a specific histological structure, can lead to the accumulation of EPS, thereby increasing the risk of biofilm formation. Streptococcus is one of the bacterial groups known to have the ability to produce biofilms. Bay leaves (Syzygium polyanthum (Wight) Walp), a member of the Syzygium genus that has been widely used in treating infectious diseases, both traditionally and medically, due to their eugenol content, are suspected to have antibiofilm activity. This study aimed to prove the antibacterial and antibiofilm effects of ethanol extract of bay leaves against Streptococcus sanguinis and Streptococcus mutans bacteria. This study used a post-test only controlled group design, with a microtiter plate assay technique, and determination of MIC50 and MBIC50 through a probit test. The bacterial test results showed that the MIC50 values for Streptococcus sanguinis and Streptococcus mutans were 37.57% and 9.65%, respectively, while the MBIC50 values were 6.41% and 29.98%, respectively. The coefficient of determination (R2) values for both test bacteria, in both the antibacterial and antibiofilm tests, were close to 1. Thus, it can be concluded that bay leaf extract is effective as an antibacterial and antibiofilm agent against Streptococcus sanguinis and Streptococcus mutans bacteria, with a stronger antibiofilm effect than its antibacterial effect.